Filmer la ville et ses acteurs ordinaires - Rouba Kaedbey (EchoGéo)
This article examines the use of an audiovisual approach in the context of a thesis in urban geography and planning. Based on her own experience of filmmaking, the author defends the idea that film is a perfectly appropriate tool to highlight issues of social geography. It makes visible and audible hidden aspects of social space, thus participating in the production of knowledge. From a methodological point of view, the article points out the way in which the different phases of the filmmaking process - from the shooting to the broadcasting - serve to feed the thesis. Beyond its theoretical and methodological advantages, a research film requires a committed approach that can take various aspects, as shown by the author.